Unia Europejska jako wspólnota oparta na wartościach — znaczenie dla państw sąsiadujących - Cieśliński, Aleksander (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
There is no doubt that the European Union is to be considered a community based on values — especially since the significant reforms introduced by the Lisbon Treaty in Art. 2 TEU, which not only includes their wide list, but first of all names them in this exact way. They are treated as developed from the cultural, religious and humanist inheritance of Europe, but are rather typical for modern western societies with the emphasis put on human dignity, equality, pluralism and tolerance. What is important, their meaning is not limited only to the EU’s territory or Member States themselves. According to the Treaties, in its relations with the wider world, the EU shall uphold and promote its values and in case of neighboring countries to develop a special relationship, aiming to establish an area of prosperity and good neighborliness, founded on them. Such an idea seems to be essential for future candidates states to since the leading Treaty condition of the application to become an EU Member State is respect for values.
Keywords: EU values; Lisbon Treaty; fundamental rights; EU neighbors; EU membership